Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Given equation can be written as, \frac{(x-1)^{2}}{(\sqrt{5})^{2}}+\frac{(y-2)^{2}}{(3)^{2}}=1 .
Here, a=√5 and b=3 then e=\sqrt{\frac{b^{2}-a^{2}}{b^{2}} since b>a.
Hence, eccentricity, e=⅔.
1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts